Designing, Planning & Implementation of IT Infrastructure & Security for A Brokerage House - Muhammad Tahir; Asim Rafiq; Danish Hassan (Sir Syed University Research Journal of Engineering and Technology)
M-Commerce is widely known as wireless network technology, use as the essential means of communication for business transactions. Mobile commerce is seen as an augmentation of E-commerce empowered by cell phones. Transactions either indirectly or directly carried out or supported through mobile phones. ABC Brokerage House is the pioneer in Online Trading Services. In online trade, customers can trade using the online trade software and website. Before switching users, from traditional trading system to mobile trading system, the weaknesses of infrastructure, security breaches, and risk factors should be considered carefully. The infrastructure solution should be designed with respect to interoperability, security, scalability, non-repudiation of ABC Brokerage House on the behalf of best practices for Mobile Commerce Trading System. The solution has its distributed nature and is a suitable architecture for managing business processes of ABC Stock Brokerage House. The solution is well planned, designed and it is in accordance with ISO recommendation. The solution provides more flexibility and also provides redundancy by using clustering of database server. The proposed solution provides more flexibility and also provides redundancy plan and clustering of database server. This solution also switches ABC Brokerage House infrastructure to the real world infrastructure by removing risk factors and implementing the latest technologies.